Social developments in the European Union 2013 (Brussels, 2014)
" The European Union has gone through a crucial period marked by growing anti-EU sentiments and the difficult implementation of its largely renewed socio-economic governance. After years of in-depth innovations and the hope of reinvigorating the E(M)U social dimension, European institutions have engaged in a lively debate on how to exit the recession and relaunch the integration project. While most Member States have continued to pursue punitive austerity programmes – at a time when 27 million Europeans are unemployed and a quarter of the EU population is at risk of poverty – most stakeholders (namely the trade union movement) and policymakers agree on the need for an EU-driven growth strategy.